2011
DOI: 10.1097/mpa.0b013e3182217f17
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyethyl Starch Resuscitation Reduces the Risk of Intra-Abdominal Hypertension in Severe Acute Pancreatitis

Abstract: Fluid resuscitation with HES in the early stages of SAP can decrease the risk of intra-abdominal hypertension and reduce the use of mechanical ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 33 publications
0
52
0
Order By: Relevance
“…Surprisingly, there are only 2 studies comparing the use of alternate fluids and they compared different types. 20,21 The study by Du et al 20 found that resuscitation with Ringer lactate + hydroxyethyl starch resulted in lower rates of intra-abdominal hypertension and the requirement for mechanical ventilation when compared to with resuscitation with Ringer lactate alone. The study by Wu et al 21 found that resuscitation with Ringer lactate reduced systemic inflammation when compared with resuscitation with normal saline.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Surprisingly, there are only 2 studies comparing the use of alternate fluids and they compared different types. 20,21 The study by Du et al 20 found that resuscitation with Ringer lactate + hydroxyethyl starch resulted in lower rates of intra-abdominal hypertension and the requirement for mechanical ventilation when compared to with resuscitation with Ringer lactate alone. The study by Wu et al 21 found that resuscitation with Ringer lactate reduced systemic inflammation when compared with resuscitation with normal saline.…”
Section: Discussionmentioning
confidence: 97%
“…Another limitation of this review stems from the inherent variability in the severity of AP included in the different studies. While 6 studies included only severe AP, [9][10][11]20,23,26 9 studies included all patients within a range of AP severity. 7,8,21,22,24,25,27,28,44 Furthermore, even the group of patients with severe AP was not homogeneous, as various definitions of severity were applied.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have been conducted on the effects of parenteral fluids on the outcome of AP [69][70][71] . A multicenter study of 40 cases of adult AP showed a significant decrease in SIRS incidence with…”
Section: (Grade 2/b Full Agreement)mentioning
confidence: 99%
“…In experimental AP, FT with crystalloid associates with reduced survival compared with hypertonic saline [109] or various colloids, including albumin [72], high molecular weight (HMW) dextrans [110e117], fresh frozen plasma [118], and purified bovine hemoglobin [119,120]. Investigators of the few RCTs of FT in AP [78,121,122] report that lactated ringers (LR) vs. normal saline associates with less frequent SIRS [78] and FT with hydroxyethyl starch (HES) vs. LR associates with less intra-abdominal hypertension [121]. Results of more conclusive critical care RCTs, however, indicate no benefit of any colloid (including HES) vs. crystalloid [123e128].…”
Section: Fluid Therapy (Ft)mentioning
confidence: 99%